505 What are good jobs? a european perosh perspective. (24th April 2018) - Fishwick, David; Robinson, Edward; Wiezer, Noortje; Mockalo, Zofia; Grosjean, Vincent; Andersen, Lars L
Abstract : Introduction: PEROSH stands for the Partnership for European Research in Occupational Safety and Health. The work of this group relates to developing a European perspective concerning wellbeing, and importantly organising worker wellbeing conferences. Our most recent conference developed a 'Good Jobs' theme. Methods: Wellbeing experts participated in a knowledge café event, rotating between three semi-structured discussions relating to: what makes a good job, roles of leadership and good jobs in harsh economic times. Results: What makes a good job ; individual factors including autonomy, support, recognition, development through workplace learning programmes, optimum work-life balance, adaptation to different working life phases, adequate financial rewards and the ability to focus on primary task were identified as important. The nature of the work was felt important to result in engagement and challenge, be safe and inclusive, and both be meaningful and personally flexible. Leadership roles ; associated with good jobs included the ability to creatively motivate and engage workers, provide social support, coaching, mentoring and empathy, and foster a good balance between shareholder and stakeholder requirements. Participation, instead of command and control, appeared key, as did recognition and management of interpersonal conflicts at work. Leaders were favoured who allowed autonomy, facilitated development and progress, and were seen as role models. Good jobs in harsh economic times ; were identified to require many individual attributes centred around purposeful individual rewards, work attributes that considered issues that did not cost money to improve (e.g. better communication around change), and work site attributes centred around investing in people as important resources and innovative labour relations. Discussion: PEROSH has successfully developed a view relating to what constitutes a good job. It is hoped that the output from this process will help shape the future workplace and employment policies of each of the represented European countries.